Diurnal Cycle of Translaminar Pressure in Nonhuman Primates Quantified With Continuous Wireless Telemetry - Jasien, Jessica V. (Invest Ophthalmol Vis Sci, 2020)
PURPOSE: Recent retrospective clinical studies and animal experiments have suggested that cerebrospinal fluid pressure (CSFP) is important in glaucoma pathogenesis. Intraocular pressure (IOP) and CSFP are the driving components of the translaminar pressure (TLP), which directly effects the optic nerve head. This study measured the diurnal cycle of TLP using continuous wireless telemetry in nonhuman primates (NHPs), a common animal model of glaucoma. METHODS: We have developed an implantable wireless telemetry system based on a small piezoelectric pressure transducer with low drift. Unilateral IOP was measured in the anterior chamber of the eye, and intracranial pressure (ICP, a surrogate measure of CSFP) was measured in the brain parenchyma in four awake, behaving NHPs for periods of 22 to 281 days. IOP and ICP telemetry transducers were calibrated with direct pressure measurements in the eye (every 2 weeks) and brain (monthly). TLP was quantified in real time as IOP-ICP, and hourly means of IOP, ICP, and TLP were analyzed. RESULTS: Results show that mean ICP is significantly higher by an average of 4.8 ± 0.8 mmHg during sleeping hours in NHPs (P < 0.01). IOP showed a small but significant nocturnal elevation in two of four animals despite NHPs sleeping upright (P < 0.05). TLP was significantly lower during sleep (7.1 ± 0.6 mmHg; P < 0.01) than when the animals were awake and active (11.0 ± 0.9 mmHg), driven primarily by the large increase in ICP during sleep. CONCLUSIONS: The 56% increase in TLP during waking hours in NHPs matches the increase in TLP due to postural change from supine to upright reported previously in humans.